Economics bridge between theory and practice of Sustainable built environment: a case for marginal benefit and marginal cost - Mohd Zaki, Ar Wan Rahmah; Nawawi, Abdul Hadi; Sh Ahmad, Sabarinah (2008)

(untitled)
Common economic gauges that validate Sustainable Built Environment (SBE) in households may cause for such projects to be shelved especially when the result of commercial feasibility study does not favour the stakeholders. It is a fact that the capital cost of Energy Efficient (EE) equipment and Renewable Energy (RE) system are more expensive than the conventional methods. However, SBE is now necessary and the gap between theory and practical of SBE in relation to economics aspect must be narrowed. The economics of SBE must not only assert the environmental implication but also make tangible its benefit to the household for championing the cause. In Economics, Marginal Cost (MC) and Marginal Benefits (MB) measure additional benefits of every additional costs of investment at a specific level of production and consumption; and Economists suggests that effective gain and loss must be compared to the status quo, i.e., Relative Position (RP). These Economics theories of MC, MB and RP are adapted to measure the progression of SBE with regards to lighting requirements in a living/dining area simulated to represent two types of houses: with and without Passive Architecture (PA) design strategies. Both are applied with conventional incandescent light bulbs and EE light fittings as well as RE in lieu of the mains electricity supply. The comparative approach shows the value of MB and MC at every stage of the SBE progression and this enables the household to make informed decision at a margin. The result suggests that the value of MB is more than MC when both cases use EE light fittings, i.e., approximately RM2 gain for every RM1 cost. It is also found that RE benefits the household more in PA case. This approach makes economic sense in so far encouraging household to opt for SBE.